Modelos preditivos para a ocorrência de mucisote oral grave em pacientes pediátricos oncológicos durante o tratamento quimioterápico - Ribeiro, Isabella Lima Arrais (2015)
Severe oral mucositis constitutes a condition that often affects children and adolescents undergoing chemotherapy. This study aimed to construct statistical models for onset of severe oral mucositis in cancer pediatric patients from own variables of the patient and related to chemotherapy treatment regimen in order to guide the oral health decision making in disease prevention the oral mucosa during chemotherapy. This is a longitudinal, prospective and observational study, where oral mucositis was monitored during chemotherapy in 105 children and adolescents assisted in Napoleão Laureano Hospital between april 2013 and july 2015. It was evaluated by multiple regression binary logistic the association of different variables to the occurrence of severe oral mucositis (MOG) in accordance with the identification indicated by Oral Assessment Guide (OAG) modified in 10 different evaluation periods from the start of chemotherapy. Analyses were performed by the backward method, the R (3.1.3) software, adopting a 5% significance level. Over the 10 consecutive weeks of evaluation, it was observed that: in the 1st week of chemotherapy, being female (OR = 5.84), black skin color (OR=14.85) as well as be taking chemotherapy the class of antimetabolites (OR = 3.52), depending on the increase of time after drug administration (OR=1.13), were risk factors for the occurrence of MOG, whereas in the 2nd week, risk was associated with the fact that the child / adolescent be black skin color (OR=3.53). In the 3rd week, be blood group type B (OR=4.19) was a risk factor, while the increase in blood creatinine, a protective factor (OR = 0.67).In the 4th week, time since last chemotherapy was a protective factor (OR=0.92), as well as 8 weeks (OR=0.93). On the 5th week of chemotherapy, the use of chemotherapeutic agents from the class of natural products (OR=0.19) was considered a protective factor, while the increase in the number of platelets (OR=1.04) was considered a risk factor. In the 6th week, so chemotherapy Antimetabolites type (OR=5.80), and the increase of leukocytes (OR=1.06) and blood creatinine (OR=1.60) were considered risk factors, as well as also the increase of creatinine 7 review period (OR=1.46). For the first 8 weeks of chemotherapy pediatric cancer patients was possible to build predictive models for the occurrence of severe oral mucositis from the patient's own variables and related to chemotherapy treatment regimen. It was concluded that own patient factors such as being female, color black skin, blood group type B and increase in blood creatinine level were associated with increased odds of patients presenting to MOG. As for the treatment, the more likely development of MOG were related to chemotherapy class of Antimetabolites.